2022
DOI: 10.1186/s40337-022-00630-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum and plasma levels of brain-derived neurotrophic factor in individuals with eating disorders (EDs): a systematic review and meta-analysis

Abstract: Background Brain-derived neurotrophic factor (BDNF) is essential for neuronal survival, differentiation, development, and plasticity. Evidence suggests that fluctuations in peripheral levels (i.e., plasma or serum) of BDNF are associated with eating behaviors. Nevertheless, the findings are inconsistent. The purpose of this study is to determine if serum or plasma levels of BDNF are altered in individuals with eating disorders (EDs) compared to controls. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 65 publications
0
14
1
4
Order By: Relevance
“…However, although the study of Shobeiri et al [ 1 ] has many strengths including state of the art meta-analytic methods and solid statistical analysis (e.g., leave-one-out analysis), we have some critical concerns regarding the study selection process, and consequently, the results obtained and the conclusions that can be drawn from them. Shobeiri et al [ 1 ] state that studies were only included if they (a) were observational, measuring BDNF levels in individuals with EDs without other psychiatric or neurological comorbidities and (b) provided sufficient data, i.e., number of participants, mean, and standard deviation (SD) of BDNF levels.…”
Section: Inclusion Of Studies For the Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…However, although the study of Shobeiri et al [ 1 ] has many strengths including state of the art meta-analytic methods and solid statistical analysis (e.g., leave-one-out analysis), we have some critical concerns regarding the study selection process, and consequently, the results obtained and the conclusions that can be drawn from them. Shobeiri et al [ 1 ] state that studies were only included if they (a) were observational, measuring BDNF levels in individuals with EDs without other psychiatric or neurological comorbidities and (b) provided sufficient data, i.e., number of participants, mean, and standard deviation (SD) of BDNF levels.…”
Section: Inclusion Of Studies For the Meta-analysismentioning
confidence: 99%
“…However, although the study of Shobeiri et al [ 1 ] has many strengths including state of the art meta-analytic methods and solid statistical analysis (e.g., leave-one-out analysis), we have some critical concerns regarding the study selection process, and consequently, the results obtained and the conclusions that can be drawn from them. Shobeiri et al [ 1 ] state that studies were only included if they (a) were observational, measuring BDNF levels in individuals with EDs without other psychiatric or neurological comorbidities and (b) provided sufficient data, i.e., number of participants, mean, and standard deviation (SD) of BDNF levels. However, using the search criteria applied by Shobeiri et al [ 1 ], we identified six studies that either met inclusion criteria [ 2 , 3 ], would have met them if the authors had requested data from the investigators [ 4 , 5 ], or simply calculated SDs from the reported statistical measures (i.e., 95% confidence intervals, interquartile ranges) [ 6 , 7 ].…”
Section: Inclusion Of Studies For the Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations